STRUCTURE-FUNCTIONAL SELF-ORGANIZATION OF ZrO2–SiO2:Sn(IV) SYSTEM - Trachevskiy, Volodymyr; Prudius, Svitlana; Mylin, Artur (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2022)
The study is devoted to the solution of one of the actual problems of materials science – the conscious management of the fundamental properties of solids. It is based on the development of an algorithm for creating both on intergranular surfaces and in the volume of particles nanosized inclusions, crystallites, structural defects. Taking into account the accumulated results of systematic studies of simple, binary systems as previous experience for further design of more complex systems, for correctly overcome the fundamental disadvantages, associated with the inconsistency of multicomponent systems, the sequence of physico-chemically substantiated technological stages on the way of formation of functional architecture has been formulated. The coevolutionary concept of self-organization of chemical systems is also formulated, according to which the regulation of the course of structural-functional reorganization processes takes place by two mechanisms: adaptation and bifurcation. Taking into account the physicochemical properties, optimal conditions for the formation of element oxide clusters and the peculiarities of interparticle interaction, the course of structural and functional self-organization – response of colloidal solutions of a multicomponent system to directionally initiated changes in the characteristics of the dispersed reaction medium and, accordingly, the parameters of particles that are deliberately designed in this way (size, shape, composition, structure of their ensembles), as well as the effect on interparticle distances, hierarchy of structural levels, the action of concentration and temperature factors and the introduction of a modifying reagent were diagnosed by various measurements. The driving forces (electronegativity, competitive rearrangements) and tendencies of energy-supplied bifurcation formation of coordination polyhedra of structure-forming ions in multicomponent ensembles were identified, namely, the pathways of directed initiated rearrangement of the atomic architecture with the organization of oxygen-unsaturated zirconium-containing sites, which determined the matrix formation with practically significant catalytic activity.